2006
DOI: 10.1128/jb.01059-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of BicistronicspeBandprsAGene Expression in the Group A Streptococcus

Abstract: Severe, invasive group A streptococcal infections have reemerged worldwide, and extracellular toxins, including streptococcal pyrogenic exotoxin B (SpeB), have been implicated in pathogenesis. The genetic regulation of SpeB is not fully understood, and the mechanisms involved in the processing of the protoxin to its enzymatically active form have not been definitively established. The present work demonstrated that the genes encoding SpeB (speB) and a peptidyl-prolyl isomerase (prsA) constitute an operon with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 44 publications
4
67
0
Order By: Relevance
“…The genomic coordinates are shown and the putative promoters and terminators are indicated. prsA (encoding the foldase protein PrsA) is involved in the maturation of SpeB protease [28]. SPy_2038 was described to encode an inhibitor of SpeB protease activity [58].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genomic coordinates are shown and the putative promoters and terminators are indicated. prsA (encoding the foldase protein PrsA) is involved in the maturation of SpeB protease [28]. SPy_2038 was described to encode an inhibitor of SpeB protease activity [58].…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to provide coherence for future studies – the annotation of the speB 5′ UTR has been inconsistent in previous works [23,2628] –, we first determined speB transcript boundaries. We demonstrated that RNase Y and so far unidentified RNase(s) process the 5′ UTR of speB mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that Nuc requires PPIase activity for optimal protein folding (3,4). Based on this observation and the fact that PPIase-mediated folding is required for subsequent activity of secreted virulence factors in a number of bacterial pathogens (8)(9)(10)(11)(27)(28)(29)(30), we hypothesized that a staphylococcal PPIase may be required for the activity of Nuc. To begin to investigate this, we examined the genome of the community-associated methicillin-resistant S. aureus (MRSA) isolate USA300 for genes that encode PPIase enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought to assist in the refolding of proteins as they are exported from the bacterial cell. PrsA has been well studied in two bacterial pathogens, Listeria monocytogenes and Streptococcus pyogenes, where alteration of prsA levels (either increased or decreased) leads to defects in protein secretion and/or virulence of the organism (7)(8)(9)(10). The cyclophilins are by far the least-studied and least well understood group of PPIases in bacteria.…”
mentioning
confidence: 99%